South American resourcescapes: geographical perspectives and conceptual challenges - Coy, Martin; Ruiz Peyré, Fernando; Obermayr, Christian (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Once again, resources are at the centre of scientific and public interest. From 2000 onwards, soaring commodity prices and the unrestricted proliferation of extractive activities have caused significant spatial, political and socio-economic consequences in producer countries with large extractive economies. We exemplify these consequences by telling the resource stories of South American countries, where the ‘resource curse’ and the internal logics of extractive economies have been deeply inscribed in the socio-economic, cultural and territorial orders since colonial times. Inspired by Swyngedouw (1999), we adopt his notion of ‘waterscapes’ and argue that a deeper, holistic comprehension of resource landscapes (i.e. resourcescapes) is necessary for the understanding of the multidimensional and contradictory nature of resources and possible transitions towards a sustainability-oriented transformation. We suggest that such a framework should be based on Political Ecology, but could also be enriched by taking up other impulses from contemporary poststructuralist and critical geographies and from South American debates on (neo-) extractivism. Starting with a conceptualization of the term ‘resource’, we illustrate historical trajectories and changing perspectives of societal relations with resources in South America. After that, we review conceptual debates in social sciences and ask how these concepts could give impulses for a more holistic framework.